MAIN TASKS OF THE CURRENT REPAIR OF THE ROAD: TO ENSURE THE GOOD CONDITION OF THE RAILWAY - Choriyev Rustam Alisher ugli; Samandarov Khushnudbek Odilbekovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
the article describes the main tasks of the current repair of Railways, the fault levels of the road and the basics of ensuring traffic safety.